Beyond the core face-processing network: Intracerebral stimulation of a face-selective area in the right anterior fusiform gyrus elicits transient prosopagnosia. (November 2015) - Jonas, Jacques; Rossion, Bruno; Brissart, Hélène; Frismand, Solène; Jacques, Corentin; Hossu, Gabriela; Colnat-Coulbois, Sophie; Vespignani, Hervé; Vignal, Jean-Pierre; Maillard, Louis
Abstract: According to neuropsychological evidence, a distributed network of regions of the ventral visual pathway – from the lateral occipital cortex to the temporal pole – supports face recognition. However, functional magnetic resonance imaging (fMRI) studies have generally confined ventral face-selective areas to the posterior section of the occipito-temporal cortex, i.e., the inferior occipital gyrus occipital face area (OFA) and the posterior and middle fusiform gyrus fusiform face area (FFA). There is recent evidence that intracranial electrical stimulation of these areas in the right hemisphere elicits face matching and recognition impairments (i.e., prosopagnosia) as well as perceptual face distortions. Here we report a case of transient inability to recognize faces following electrical stimulation of the right anterior fusiform gyrus, in a region located anteriorly to the FFA. There was no perceptual face distortion reported during stimulation. Although no fMRI face-selective responses were found in this region due to a severe signal drop-out as in previous studies, intracerebral face-selective event-related potentials and gamma range electrophysiological responses were found at the critical site of stimulation. These results point to a causal role in face recognition of the right anterior fusiform gyrus and more generally of face-selective areas located beyond the "core" face-processing network in the right ventral temporal cortex. It also illustrates the diagnostic value of intracerebral electrophysiological recordings and stimulation in understanding the neural basis of face recognition and visual recognition in general.